Transfer of Tissue Factor from Platelets to Monocytes: Role of Platelet-Derived Microvesicles and CD62P - Scholz, Thomas; Temmler, Uta; Krause, Siegfried; Heptinstall, Stan; Lösche, Wolfgang (Thrombosis and Haemostasis, 2002)
Tissue factor (TF) is the most important initiator of intravascular coagulation. Platelets contribute to TF exposure on monocytes, but the mechanism is not completely understood. Here we examined the possibility that platelets may release TF that can be transferred to monocytes by platelet-derived microvesicles. When human citrated platelet-rich plasma was incubated with collagen there was an increase in the plasma levels of TF and CD62P. Incubation of plasma obtained from collagen-stimulated PRP with a sediment of red and white blood cells resulted in an increase in the number of monocytes that express TF, CD62P and the platelet-specific antigen CD42a on their surface. This transfer of platelet-derived antigens to monocytes was reduced when CD62P was blocked by a specific antibody or when platelet-derived microvesicles were removed from the plasma either by high speed centrifugation (17,500 X g for 30 min) or by filtration (pore size 0.2 µm). The data indicate that platelet-derived microvesicles that are released from collagen-stimulated platelets may carry TF, CD62P and CD42a and may transfer these antigens to the surface of monocytes. The interaction of platelet-derived microvesicles with monocytes and the transfer of TF to monocytes strongly depend on CD62P.
Keywords: Cell-cell interaction; microvesicles; monocytes; platelets; tissue factor